Vascular Disease in Systemic Lupus Erythematosus. (22nd August 2012) - Pyrpasopoulou, Athina; Chatzimichailidou, Sofia; Aslanidis, Spyros
Abstract : Vascular disease, either as a direct complication of the disease or developing as an accompanying comorbidity impairs significantly the quality of life of patients with SLE and represents the most frequent cause of death in established lupus. This paper aims to give an overview of the prevalence of the different forms of vasculopathy that can be encountered in a lupus patient, describe their pathogenesis, and address their impact on disease severity and outcome.